TINJAUAN ATAS PROSEDUR PEMBERIAN PINJAMAN: PADA KOPERASI CREDIT UNION BINA SEROJA - Narsiana Melti; Posma Sariguna Johnson Kennedy (Buletin Ekonomi, 2018)
practice of field work carried out in the Cooperative Credit Union Bina Seroja in East Jakarta aisle flow. The field work was conducted to determine the procedures for granting loans to cooperatives Credit Union Bina Seroja. Data obtained through field work and interviews credit team. Economic problems and needs urgent community and supported the low income of the communities that do not fit the needs often makes people have difficulty in providing capital Therefore, the provider of capital is needed because with the capital providers can support the path of economic activity. One form is a cooperative fund providers by providing loans. In lending procedures needed in order to avoid obstacles that can menyebebkan emergence of problems that can harm the cooperative itself. However Outline procedures for granting loans that have been implemented in co-operative Credit Union Bina Seroja fulfill criteria apply lending procedures generally.Keywords : economic problem, procedures for granting loans